Compositional profile of milk round the year at Bagbabarighat milk shed area of Bangladesh - ISLAM, K M S (The Indian Journal of Animal Sciences, 2014)
Baghabarighat milk shed area (BMSA), a part of Bangladesh Milk Producers Co-operative Union Limited (BMPCUL), was selected to study the compositional aspects of milk collected over 6 year period. Average fat, SNF and TS content of milk were 5.15, 7.82 and 12.97%, respectively, over the year. Higher yield (thousand 1/day) during January (40.94) and February (41.13) and lower for July (20.47), August (17.84), September (18.59) and October (18.87), were observed. Intermediate values of production were observed for November (24.35), December (34.70), March (31.72), April (29.33), May (26.23) and June (28.14). There was slight decrease (P>0.01) in fat value in January (5.02%) and February (4.94%) when the yield was highest. Feed availability increases milk yield, live weight gain and dry matter intake of cows. But no specific changes seemed to have taken place throughout the year for fat, solids-not-fat and total solid value. A large variation (P<0.01) was observed for the amount of milk collected throughout the year. Mentioned parameters were highly correlated either negatively (fat and SNF, fat and milk yield, SNF and TS and also TS and milk yield) or positively (fat and TS, SNF and milk yield) all over the year.